Unfolding the Influence of Metal Doping on Properties of CsPbI3 Perovskite. Issue 9 (9th August 2020) - Kajal, Sandeep; Kim, Junu; Shin, Yun Seop; Singh, Aditya Narayan; Myung, Chang Woo; Kim, Jin Young; Kim, Kwang S.
Abstract: Low‐temperature α‐phase stabilization using HI or zwitterions in cesium lead iodide (CsPbI3 ) endures the metastable phase properties but is thermally unstable. Doping with a small amount of heterovalent metals (i.e., Bi 3+, Sb 3+ ) in CsPbI3 has been assumed to stabilize the α‐phase, while here this assumption is challenged. It is demonstrated that heterovalent metal ion doping stabilizes β‐CsPbI3 at low temperatures without replacing the Pb 2+ cations, while divalent cations (i.e., Ba 2+, Sr 2+, and Sn 2+ ) doping stabilizes the α‐CsPbI3 by replacing the Pb 2+ cations. This finding is demonstrated by both theoretical and experimental results. It is also found that the divalent cations stabilize α‐CsPbI3 films, making thermally stable at high temperatures, whereas heterovalent metal‐doping stabilizes β‐CsPbI3 films, making metastable. The doping influence on crystal grains and the chemical composition of thin films is discussed. In particular, the charge dissociation kinetics for the Sr doped thin film are much enhanced than α‐CsPbI3 and Ba doped thin films, also the initial results of the fabricated perovskite red‐light‐emmiting diode suggests that the Sr‐doped thin films would be more suitable for the device fabrication. These findings will guide a way for further development in thermally and air‐stable optoelectronic devices. Abstract : The photoactive phase of CsPbI3 stabilized with various metal dopants. The doping of Sr 2+, Ba 2+, or Sn 2+ stabilizes the α‐phase, while that of Sb 3+ or Bi 3+ stabilizes the β‐phase. Sn 2+ and Ba 2+ doped thin films exhibit poor air stability compared to other metal dopants, while Sb 3+ or Bi 3+ doping stabilizes CsPbI3 thin films, making them metastable.